Coronavirus Disease 2019 Vaccination for Cancer Patients: Risk or Benefit? - Laporte, Bruno Eduardo Pereira; Laporte, Estela Gelain Junges; Aarestrup, Paula Fonseca; Aarestrup, Matheus Fonseca; Aarestrup, Fernando Monteiro (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective The aim of the present study is to list the published clinical trials on coronavirus disease 2019 (COVID-19) vaccines, to describe the mechanism of action of the identified vaccines, and to identify protocols regarding safety, status, and prioritization of cancer patients for vaccination.Methods This is a systematic review with a limited literature search conducted by an information specialist; key resources such as PubMed and websites of major cancer organizations were searched. The main search terms were COVID-19, vaccination, cancer, and breast and gynecological cancers.Results Cancer patients infected with the new coronavirus are at high risk of complications and death, but we still know little about the risks and benefits of vaccination for COVID-19 in these patients. In an ideal scenario, all cancer patients should have their immunization status updated before beginning treatment, but this is not always possible.Conclusion Patients with breast or gynecological cancers who are receiving treatment or are in the 5-year posttreatment period should be included in the priority group for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccination.
Keywords: cancer; COVID-19; vaccination; protocols